2013
DOI: 10.3233/asy-131162
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior of a suspension of oriented particles in a viscous incompressible fluid

Abstract: A viscous incompressible fluid with a large number of small axially symmetric solid particles is considered. It is assumed that the particles are identically oriented and under the influence of the fluid move translationally or rotate around a symmetry axis with the direction of their symmetry axes unchanged. The asymptotic behavior of oscillations of the system is studied, when the diameters of particles and distances between the nearest particles are decreased. The equations, describing the homogenized model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Analogously to [1], [2], [3], [4] and [6], it may be shown that the family of solutions u ε (x, λ) of the problem (4.1)-(4.5) is analytic in the domain {Reλ > 0}. Moreover, in this domain the following estimate holds:…”
Section: Consider a Partition Of The Domain ω By Non-intersecting Cub...mentioning
confidence: 95%
See 2 more Smart Citations
“…Analogously to [1], [2], [3], [4] and [6], it may be shown that the family of solutions u ε (x, λ) of the problem (4.1)-(4.5) is analytic in the domain {Reλ > 0}. Moreover, in this domain the following estimate holds:…”
Section: Consider a Partition Of The Domain ω By Non-intersecting Cub...mentioning
confidence: 95%
“…Due to the estimates (6.3) and (6.4), we can apply the inverse Laplace transform (see, for example, [14] and [8]) and prove, thereby, the statement of Theorem 2 (see details in [1], [2], [3], [4] and [6]).…”
Section: Consider a Partition Of The Domain ω By Non-intersecting Cub...mentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of particle concentration was also considered in [20,21]. Rigorous asymptotical homogenization strategies for suspensions were used for example in [12,3]. The work by Junk & Illner [11] deals with the strict asymptotic derivation of Jeffery's equation, using expansions in the small size ratio (ratio between the characteristic length scale associated to the particle and the one associated to the fluid).…”
Section: Introductionmentioning
confidence: 99%